Investigation of extreme ultraviolet radiation of highly charged Mo ions from a laser-produced plasma. (December 2021) - Bakhiet, Mohammedelnazier; Su, Maogen; Cao, Shiquan; Wu, Yanhong; Li, Maijuan; He, Siqi; Liu, Jinzhu; Dong, Chenzhong
Highlights: The spectra of molybdenum (Mo) emitted by a nanosecond Nd:YAG laser-produced plasma, have been measured in the 6.7–14.3 nm region using a spatio-temporally resolved laser-produced plasma spectroscopy technique. The calculations were made for the whole observed distinctive features that arose from the 4s- n p, 4p- n d, and 4p- m s resonance transition arrays of the Mo 7+ -Mo 12+ ions. Double excitations (inner-shell excitations) of Mo 12+ - Mo 14+ ions were also considered. Numerous previously unidentified lines have been identified with the aid of the Hartree-Fock (HF) method within the pseudo-relativistic corrections (HFR) using Cowan's codes. The steady-state collisional-radiative (CR) model was devoted to obtain the plasma parameters. The observed spectrum was compared to a spectrum synthesized with calculated data from HFR. The agreement between the simulated spectra and experimental results is excellent. Abstract: Spectra of highly-charged Mo ions excited in the 6.7–14.3 nm wavelength region by focusing Nd:YAG laser light pulses ( λ =1064 nm, 10 ns) have been recorded and investigated. A spatio-temporally resolved laser-produced plasma spectroscopy technique was used. The observed spectra are composed of many lines that correspond to Mo 7+ -Mo 12+ ions belonging to the 4s- n p, 4p- n d ( n  = 5–8), and 4p- m s ( m  = 6–8) transition arrays. Only 4p-(5, 6)s and 4p-(5, 6)d resonance transition of Mo 7+ and Mo 8+ were analyzed before. The spectrum investigations were based on the Hartree-Fock (HF) method within the framework of the pseudo-relativistic corrections (HFR) using Cowan's codes. Double excitation in Mo 12+, Mo 13+, and Mo 14+ were also worthy of inclusion because of their important contributions. To obtain the best fitting with the spectral features, the possible contributions from the 4s4p k 4d metastable state ions within the plasma were included. Comprehensive calculations were performed and several previously unclassified lines have been identified for the first time. A steady-state collisional-radiative (CR) model was devoted to obtaining the plasma parameters and interpreting the emitted spectrum. The theoretical simulated spectrum agrees reasonably well with the experimental profile, which can indicate the possibility of use for plasma diagnostics. The results should be beneficial for future assessment and comparisons as well as spectroscopic diagnostics of hot plasmas in tokamak plasmas and fusion research.